Increasing participation in cervical cancer screening: Offering a HPV self‐test to long‐term non‐attendees as part of RACOMIP, a Swedish randomized controlled trial. Issue 9 (31st October 2013) - Broberg, Gudrun; Gyrd‐Hansen, Dorte; Miao Jonasson, Junmei; Ryd, Mare‐Liis; Holtenman, Mikael; Milsom, Ian; Strander, Björn
<x xml:space="preserve">Abstract</x> RACOMIP is a population‐based, randomized trial of the effectiveness and cost‐effectiveness of different interventions aimed at increasing participation in a well‐run cervical cancer screening program in western Sweden. In this article, we report results from one intervention, offering non‐attendees a high‐risk human papillomavirus (HPV) self‐test. Comparison was made with standard screening invitation routine or standard routine plus a telephone call. Women (8, 800), aged 30–62, were randomly selected among women without a registered Pap smear in the two latest screening rounds. These women were randomized 1:5:5 to one of three arms: 800 were offered a high‐risk HPV self‐test, 4, 000 were randomized to a telephone call (reported previously) and 4, 000 constituted a control group (standard screening invitation routine). Results were based on intention to treat analysis and cost‐effectiveness was calculated as marginal cost per cancer case prevented. The endpoint was the frequency of testing. The total response rate in the self‐testing arm was 24.5%, significantly higher than in the telephone arm (18%, RR 1.36, 95% CI 1.19–1.57) and the control group (10.6%, RR 2.33, 95% CI 2.00–2.71). All nine women who tested positive for high‐risk HPV attended for a cervical smear and colposcopy. From the health‐care sector perspective, the intervention will most likely lead to no additional cost. Offering a self‐test for HPV as an alternative to Pap smears increases participation among long‐term non‐attendees. Offering various screening options can be a successful method for increasing participation in this group.